Evaluasi Tingkat Kebisingan Daerah Kerja Kapal Penangkap Ikan - Yuniar Endri Priharanto; Rizqi Ilmal Yaqin; Mariandri Pasaribu; Bobby Demeianto (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
The impact of noise in the working area of fishing vessels should be understood, and effective noise reduction strategies should be identified to protect the health and performance of crew members in the workplace. This study aims to evaluate the level of noise in the working area of fishing vessels using a sound level meter during fishing operations. The study involved direct field data collection to obtain accurate and representative information on the noise levels experienced by the crew during fishing operations. Areas evaluated for noise levels include the engine room, deck, crew quarters, stern, and bow of the vessel. Data used for the study were collected from KM Nelayan Jaya, a fishing vessel equipped with a purse seine fishing gear, measuring 28.45 meters in length and powered by a 300 HP diesel engine. Noise levels were evaluated based on the IMO standard for noise exposure in the workplace, which recommends an average exposure limit of 80 dBA over 24 hours. The results of this study provide information on areas that exceed the specified standard noise levels and identify effective noise reduction strategies to protect the health and performance of crew members while improving the operational efficiency and overall sustainability of fishing vessels.